Medullary Carcinoma and Thyrocalcitonin. Issue 5623 (12th October 1968) - Tubiana, M.; Milhaud, G.; Coutris, G.; Lacour, J.; Parmentier, C.; Bok, B.
Abstract : Seven patients with medullary carcinoma of the thyroid were investigated, and the thyrocalcitonin activity of the primary tumours, metastatic deposits, and the serum was estimated. Medullary carcinomas of the thyroid with amyloid stroma contain 100 to 600 times more thyrocalcitonin than normal thyroid tissue, and lymph nodes with metastatic deposits are equally rich in the hormone. High values of thyrocalcitonin are also found in the blood of these patients. Medullary carcinoma of the thyroid with amyloid stroma is the first disease to be recognized in which there is hypersecretion of thyrocalcitonin.